2005
DOI: 10.1093/jat/29.5.370
|View full text |Cite
|
Sign up to set email alerts
|

Gas Chromatography-High-Resolution Mass Spectrometric Method for Determination of Methamphetamine and its Major Metabolite Amphetamine in Human Hair

Abstract: ]Gas chromatography-high-resolution mass spectrometric (GC-HRMS) method is presented for the qualitative and quantitative analysis of methamphetamine (MA) and its major metabolite, amphetamine (AMP), in human hair. The method procedure involves decontamination of hair with distilled water and acetone, acidic hydrolysis and extraction in the presence of the internal standard, and GC-HRMS selective ion monitoring (SIM) analysis. The limits of detection (LOD) were 9 pg/mg for MA and 21 pg/mg for AMP using a 30-mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 41 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…20 Thus, in this study, we used hair samples, which are obtained non-invasively and easily stored in a dry environment for several months. Over the years, we found that hair samples provide valuable physiological information on endogenous metabolites including steroids, 21,22 estrogens, 23,24 amphetamine metabolites 25 and cholesterol. 26 Thus, we assessed the potential of hair samples as a biological sample to analyze polyamines.…”
Section: Introductionmentioning
confidence: 99%
“…20 Thus, in this study, we used hair samples, which are obtained non-invasively and easily stored in a dry environment for several months. Over the years, we found that hair samples provide valuable physiological information on endogenous metabolites including steroids, 21,22 estrogens, 23,24 amphetamine metabolites 25 and cholesterol. 26 Thus, we assessed the potential of hair samples as a biological sample to analyze polyamines.…”
Section: Introductionmentioning
confidence: 99%